Interactive Digital Map (PELITA) of Indonesia's Cultural Diversity in Pancasila Education Subjects for Grade V Elementary School - Ni Made Putri Yuni Sridewi Indriani Wijaya; I Gusti Agung Ayu Wulandari; Ni Luh Putu Agetania (Universitas Pendidikan Ganesha, 2024)
The lack of innovative learning media related to culture affects students' level of knowledge about culture and influences the low student learning outcomes. This study aims to create a digital map learning media related to the cultural diversity of Indonesia and to test the feasibility and effectiveness of the resulting product. This research is a development study using the ADDIE model. The subjects involved in this study were three experts and 27 fifth-grade elementary school students. Data collection methods used both tests and non-tests, with instruments in the form of interviews, questionnaires, and tests. The data were then analyzed through qualitative descriptive analysis, quantitative descriptive analysis, and inferential statistical analysis.The results showed that the product feasibility test by subject matter experts, instructional design experts, and learning media experts obtained very good qualifications, so the developed product can be declared feasible to support the learning process in Pancasila Education subjects. Furthermore, the effectiveness test showed that the interactive digital map media (PELITA) on Indonesian cultural diversity was effectively applied in the fifth-grade Pancasila Education class at elementary school. Based on these findings, it can be concluded that the interactive digital map media (PELITA) is able to bring positive changes to students’ understanding of Indonesian cultural diversity and improve student learning outcomes in Pancasila Education. The implication of this research is that it can make students interested and active in participating in learning and can have a positive impact on teachers by expanding their knowledge related to the development of innovative learning media.